2016
DOI: 10.1063/1.4941337
|View full text |Cite
|
Sign up to set email alerts
|

Sub-micron solid air tracers for quantum vortices and liquid helium flows

Abstract: The dynamics of quantized vortices in superfluids has received increased attention recently because of novel techniques developed to visualize them directly. One of these techniques [G. P. Bewley et al., Nature 441, 588 (2006)] visualized quantized vortices and their reconnections in superfluid flows of (4)He by using solid hydrogen tracers of micron-size or larger. The present work improves upon the previous technique by using substantially smaller particles created by injecting atmospheric air diluted in hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 66 publications
0
19
0
Order By: Relevance
“…34 and is described in detail in ref. 33. It consists of an optical cryostat filled with liquid helium in which we inject a dilute mixture of atmospheric air in helium gas.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…34 and is described in detail in ref. 33. It consists of an optical cryostat filled with liquid helium in which we inject a dilute mixture of atmospheric air in helium gas.…”
Section: Methodsmentioning
confidence: 99%
“…Compared with these previous experimental studies we use a visualization technique that uses frozen air tracers which are much finer, described briefly in Materials and Methods and in detail in ref. 33. The technique, previously used to visualize kelvin waves (34), uses submicrometer particles injected directly in the superfluid phase, permitting the visualization of longer and straighter vortices.…”
mentioning
confidence: 99%
“…Indeed the dense packing of atoms in the nanowires "large" (in comparison with vortex core's thickness) diameter, and the presence of metallic spheres with the perfect shape and atomically smooth surface in the products were observed [16]. Our model of nanowire formation in He II based on the assumption of adiabatic regime of the coagulation process that leads to the cluster melting [16] has been recognized in several independent studies [21,22]. Nevertheless, we decided primarily to perform the systematic comparison of diameters of the nanowires grown in a low temperature experiments from various metals with those predicted for them by the model [16].…”
Section: Introductionmentioning
confidence: 96%
“…Previous work has shown that a combination of low condensible gas partial pressure and low flow rate produces solidified tracer particles with size less than one micron in He ii. 20 Therefore, a small quantity of deuterium is added to the evacuated mixture cylinder, which is then charged to 10 psig with helium gas. The mixture is supplied at a regulated pressure of 600 mbar and enters the delivery tube through a metering valve (flow coefficient C v < 0.003).…”
Section: A Visualization Experimentsmentioning
confidence: 99%
“…Visualization of grid turbulence has been successfully applied to He i, 18,19 the classical liquid phase, but applying the same to He ii requires a number of non-trivial considerations. For example, new methods for introducing passive tracer particles into He ii reduce unwanted heating and turbulence 20 and incorporating second sound attenuation would provide a more comprehensive measurement of the fluid behavior. Additionally, the magnetic coupling between the grid and drive system used for He i grid turbulence 18 is unlikely to provide careful control of the grid motion.…”
Section: Introductionmentioning
confidence: 99%